1991
DOI: 10.1017/s1049023x00038954
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hospital Ability to Provide Trauma Services: A Comparison between Teaching and Community Hospitals

Abstract: Hypothesis:Teaching hospitals (TH) can maintain the American College of Surgeons Committee on Trauma (ACSCOT) criteria for Level II trauma care more consistently than can community hospitals (CH).Methods:A retrospective analysis of 2,091 trauma system patients was done to determine if TH in an urban area are better able to meet the criteria for Level II trauma care than are CH. During the study period, a voluntary trauma plan existed among five hospitals; two TH and three CH. A hospital could accept patients t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Another analysis of the same hospitals in this study demonstrated significant differences among the hospitals in their ability to provide the trauma services required by the EMS system. 4 Two of die hospitals more successfully maintained the necessary staff and services and had less day-to-night variation in the available resources than did the rest of the participating trauma hospitals. The number of ambulances bypassing other hospitals, and coming to and going away from a specific hospital may have impact on that hospital's ability to provide trauma resources.…”
Section: Discussionmentioning
confidence: 99%
“…Another analysis of the same hospitals in this study demonstrated significant differences among the hospitals in their ability to provide the trauma services required by the EMS system. 4 Two of die hospitals more successfully maintained the necessary staff and services and had less day-to-night variation in the available resources than did the rest of the participating trauma hospitals. The number of ambulances bypassing other hospitals, and coming to and going away from a specific hospital may have impact on that hospital's ability to provide trauma resources.…”
Section: Discussionmentioning
confidence: 99%
“…In response to an increasing incidence of diversions, this community modified a previously developed inter-hospital computer system to monitor availability of trauma hospitals in a voluntary hospital trauma system prior to trauma center designation. 3 That system relied on an interhospital telecommunication system with computers located within the emergency departments of most metropolitan hospitals, all linked to the MRH. In that system, hospitals selected and displayed their respective trauma care status visually on a computer terminal.…”
Section: System Implementationmentioning
confidence: 99%
“…The reason for abdication of pediatric trauma care by pediatric facilities is complicated and probably multifactorial [6][7][8]. In 1976, the ACS Committee on Trauma published recommended guidelines for developing an organized trauma system to care for the injured patient.…”
mentioning
confidence: 99%